The Influence of Work-Life Balance, Work Innovation, Digital Work Environment, and Employee Engagement on the Performance of Generation Z Employees at PC Partner Company in Muka Kuning, Batam - Azra Khairia; Acca Maysa Sitio; Wanda Safitri; Amanda Amanda; Aisyah Livi November; Intan Ayu Wandira (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2026)
The rapid growth of Indonesia's electronics manufacturing industry, particularly in the Muka Kuning industrial area of Batam, has increased the demand for adaptive and high-performing employees, especially among the Generation Z workforce that now dominates the labor market; this condition raises the need to examine the factors that influence employee performance. This study aims to analyze the effect of Work-Life Balance, Work Innovation, Digital Work Environment, and Employee Engagement on the Performance of Generation Z Employees at PC Partner Company in Muka Kuning, Batam. The research employed a descriptive quantitative approach with multiple linear regression analysis. The population consisted of all 30 Generation Z employees at PC Partner, selected through a saturated sampling method. Primary data were collected using a Likert-scale questionnaire and processed with SPSS. The partial test (t-test) results showed that Work-Life Balance (t = 4.487), Work Innovation (t = 5.384), Digital Work Environment (t = 5.797), and Employee Engagement (t = 8.458) each had a positive and significant effect on Employee Performance. The simultaneous test (F-test) produced an F-value of 16.363 > F-table 2.76, indicating that all independent variables jointly had a significant effect on Employee Performance. The coefficient of determination (Adjusted R²) of 0.679 indicated that 67.9% of the variance in Employee Performance could be explained by these four variables.